Virginie Despentes et les récits de la violence sexuelle : une déconstruction littéraire et féministe des rhétoriques de la racialisation - Virginie Sauzon (Genre, Sexualité et Société)
In the  contemporary collective imagination, the suburbs [banlieues] epitomise masculine domination, contrasting with a society which thus appears free from sexism. As a result, creating racialized characters can confront both the salience of racist journalistic stereotypes and the intrumentalization of feminist discourse. Hence, this article focuses on the essay and fiction of Virginie Despentes, a major, yet controversial, figure in contemporary French feminism. By placing rape and sexism at the centre of her work, Despentes challenges racializing rhetoric in order to reassert the systemic, non-categorical, aspect of male domination. Rather than charging only individuals, and far from validating hypocritical securitarian discourse, Virginie Despentes’s texts contribute to the current debate in contemporary feminism in order to put an end to collaboration with racist ideologies through the voice, empowerment, and moral independence of the feminine subject.